The influence of a vertical ground heat exchanger length on the electricity consumption of the heat pumps - Michopoulos, Apostolos; Kyriakis, N. A. (My University, 2010)
The use of heat pumps combined with vertical ground heat exchangers for heating and cooling of buildings, has significantly gained popularity in recent years. The design method for these systems, as it is proposed by ASHRAE, is taking into account the maximum thermal and cooling loads of the building, the thermophysical properties of the soil at the area of installation and a minimum Coefficient of Performance (COP) of the heat pumps. This approach usually results in larger than needed length of the ground heat exchanger, thus increasing the installation cost. A new analytical simulation tool, capable to determine the required ground heat exchanger length has been developed at the Process Equipment Design Laboratory (PEDL) of the AUTh. It models the function of the system as a whole over long time periods, e.g. 20 years, using as input parameters the thermal and cooling loads of the building, the thermophysical properties of the borehole and the characteristic curves of the heat pumps. The results include the electricity consumption of the heat pumps and the heat absorbed from or rejected to the ground. The aim of this paper is to describe the developed simulation algorithm and present the results of such a simulation in a case study. It is proved that the total required length of the ground heat exchanger is less than that calculated using the common numerical method.
Keywords: Ground source heat pump; Energy analysis tool; Ground heat exchanger length